(untitled) (World Science, 2020)
The article deals with the issues of student youth activity towards Eurospace. The actualization of choreographic art at the present stage of cultural formation is substantiated. Choreographic art is analyzed as a means of integration into Eurospace. Interacting with the contemporary demands and needs of society, the art of dance influences social relations, economic order, political, ethnic and national relations. It is emphasized that choreographic art is a socially significant value and is a feeling-filled aesthetic reproduction of knowledge, skills and competences.